2023
DOI: 10.3389/fendo.2023.1117408
|View full text |Cite
|
Sign up to set email alerts
|

The association between neutrophil counts and neutrophil-to-lymphocyte ratio and stress hyperglycemia in patients with acute ischemic stroke according to stroke etiology

Abstract: Background and purposeStress hyperglycemia ratio (SHR), which is used to assess stress hyperglycemia, is associated with the functional outcome of ischemic stroke (IS). IS can induce the inflammatory response. Neutrophil counts and neutrophil-to-lymphocyte ratio (NLR) as good and easily available inflammatory biomarkers, the relationship between neutrophil counts and NLR and SHR were poorly explored in IS. We aimed to systemically and comprehensively explore the correlation between various blood inflammation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Several previous studies have demonstrated the association of NLR with unfavorable functional outcomes in AIS (Chen et al., 2020 ), acute intracerebral ICH (Zhang et al., 2023 ), and subarachnoid hemorrhage (Oliveira & Rabelo, 2023 ). It has been reported that high neutrophil counts have been found at various stages of atherosclerosis, which could damage endothelial cells (Feng et al., 2023 ). In addition, inflammation represented by NLR was also closely related with a number of vascular risk factors, including diabetes (Dung et al., 2024 ), hypertension (Xu et al., 2023 ), and hyperlipidemia (Hashemi Moghanjoughi et al., 2022 ).…”
Section: Disscusionmentioning
confidence: 99%
“…Several previous studies have demonstrated the association of NLR with unfavorable functional outcomes in AIS (Chen et al., 2020 ), acute intracerebral ICH (Zhang et al., 2023 ), and subarachnoid hemorrhage (Oliveira & Rabelo, 2023 ). It has been reported that high neutrophil counts have been found at various stages of atherosclerosis, which could damage endothelial cells (Feng et al., 2023 ). In addition, inflammation represented by NLR was also closely related with a number of vascular risk factors, including diabetes (Dung et al., 2024 ), hypertension (Xu et al., 2023 ), and hyperlipidemia (Hashemi Moghanjoughi et al., 2022 ).…”
Section: Disscusionmentioning
confidence: 99%
“…A retrospective Chinese study that included 487 patients with acute IS found that NLR and higher neutrophil counts were independently associated with the high stress hyperglycemia ratio in patients with LAA stroke [ 31 ]. SHR is used to assess stress hyperglycemia which is associated with the functional prognosis of IS [ 31 ].…”
Section: Biomarkers Associated With Laa Strokementioning
confidence: 99%
“…A retrospective Chinese study that included 487 patients with acute IS found that NLR and higher neutrophil counts were independently associated with the high stress hyperglycemia ratio in patients with LAA stroke [ 31 ]. SHR is used to assess stress hyperglycemia which is associated with the functional prognosis of IS [ 31 ]. The authors speculate that stress hyperglycemia may promote the progression of atherosclerosis by activating peripheral blood lymphocytes and neutrophils and disrupting the blood–brain barrier in IS patients with LAA [ 31 ].…”
Section: Biomarkers Associated With Laa Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Stress-induced hyperglycemia significantly influences neutrophil function, enhancing and impairing their activities over time. Initially, high glucose levels boost neutrophil functions that include chemotaxis, phagocytosis, radical oxygen species, and neutrophil extracellular traps (NETs) production [ 17 , 18 ]. Prolonged hyperglycemia results in neutrophil dysfunction manifested by the exacerbation of inflammatory mechanisms while simultaneously diminishing reparative processes of the myocardium [ 19 - 23 ].…”
Section: Introductionmentioning
confidence: 99%